Rural Finance Policies 11 - Do microfinance institutions reach the poorest? - Zeller, Manfred; Sharma, Manohar; Lapenu, Cecile; Henry, Carla (International Food Policy Research Institute, 2000)
The question raised in the title is an important one to the microfinance sector, especially since the Microcredit Summit held in Washington, DC, in 1997. In order to gain more transparency on the depth of poverty outreach, the Consultative Group to Assist the Poorest (CGAP) supported research at IFPRI during 1999 and 2000 to design and test a simple, low-cost operational tool to measure the poverty level of MFI clients relative to nonclients. This policy brief informs about the results from recent case studies on the poverty outreach of four selected microfinance institutions. The case studies were conducted for four MFIs world-wide: MFI A (Central America), MFI B (East Africa), MFI C (Southern Africa), and MFI D (South Asia).